Health-care staff beliefs and coronavirus disease 2019 vaccinations: A cross-sectional study from Iran - Mina Kianmanesh Rad; Ahmad Fakhri; LAR Stein; Marzieh Araban (Wolters Kluwer Medknow Publications, 2022)
Introduction: Health-care worker desire to receive coronavirus disease-2019 (COVID-19) vaccination can affect public perception and adoption of vaccination. The present study surveyed the health beliefs of health-care staff regarding COVID-19 vaccination. Methods: In this cross-sectional online survey conducted in Iran between May and June 2021, 537 health-care staff (73.8% females) participated. Health-care staff were assessed on the following constructs: health locus of control, trust in the health-care system, subjective norms, fear of COVID-19, attitude and feelings toward vaccination, physical distancing, intention to engage in preventative behaviors, and perceived behavioral control. Multivariate logistic regression models were used to examine the influence of demographic, clinical factors, fear of COVID-19, and health beliefs, in predicting openness toward vaccination. Results: About 67.5% of subjects received COVID-19 vaccination (first or second dose), with 57.2% reporting feeling confident in getting vaccinated and 32% expressing hesitancy in getting vaccinated. Trust in the health-care system, fear of COVID-19, and positive attitude toward vaccination were significantly higher in vaccinated participants than unvaccinated ones, P < 0.05. Conclusion: Being vaccinated and openness toward vaccination are influenced by health-care professionals' demographic and clinical characteristics, and health perceptions (i.e., fear of COVID-19). Whereas being overwhelmed with fear of COVID-19 is unadvisable, realistic concern balanced with appropriate action (e.g., vaccination) may be reasonable.